2001
DOI: 10.1128/iai.69.3.1821-1831.2001
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofMycobacterium tuberculosisGroup Organisms in Human and Mouse Joint Tissue by Reverse Transcriptase PCR: Prevalence in Diseased Synovial Tissue Suggests Lack of Specific Association with Rheumatoid Arthritis

Abstract: Infection with mycobacterial species, including

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…In addition, this association was strengthened after the observation of a seronegative form of oligoarthritis following immunotherapy with Bacillus Calmette–Guerin (BCG) vaccine [ 68 ]. Various studies have shown the presence of mycobacterium antigens in RA patients’ joints [ 69 , 70 , 71 , 72 ]. Moreover, increased levels of Abs against Mycobacterium in the serum [ 73 , 74 , 75 ] and the presence of active T cells in the synovium have been reported in RA patients [ 76 , 77 ].…”
Section: The Role Of Mycobacterial Infections In Rheumatoid Arthrimentioning
confidence: 99%
“…In addition, this association was strengthened after the observation of a seronegative form of oligoarthritis following immunotherapy with Bacillus Calmette–Guerin (BCG) vaccine [ 68 ]. Various studies have shown the presence of mycobacterium antigens in RA patients’ joints [ 69 , 70 , 71 , 72 ]. Moreover, increased levels of Abs against Mycobacterium in the serum [ 73 , 74 , 75 ] and the presence of active T cells in the synovium have been reported in RA patients [ 76 , 77 ].…”
Section: The Role Of Mycobacterial Infections In Rheumatoid Arthrimentioning
confidence: 99%
“…TI was very common in Europe in the eighteenth century and would by chance occur among those with different rheumatic diseases. However, the possibility of interactions between the immunopathogenesis of RA and the immune response to TI has long been under consideration, and needs further elucidation (13). A high prevalence of TI in the population has been suggested to induce in future generations a genetically based disposition for the development of RA, concomitant with an increased resistance against TI (14).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, guttate psoriasis is associated with streptococcal infections [12,13]. A recent study using sensitive reverse transcriptase polymerase chain reaction (PCR) analysis demonstrated the presence of numerous mycobacterial organisms in the joints of patients with RA, suggesting they may occur without causing arthritis [14].…”
Section: T-cell Activationmentioning
confidence: 99%